Flow theory – goal orientation theory: positive experience is related to athlete’s goal orientation - Stavrou, Nektarios A. M.; Psychountaki, Maria; Georgiadis, Emmanouil; Karteroliotis, Konstantinos; Zervas, Yannis (Frontiers in Psychology, 2015)
The main purpose of this study was to examine the relationship between flow experience and goal orientation theory, as well as, the differences in flow experience based on the orthogonal model of goal orientation theory. Two hundred and seventy eight athletes completed the Task and Ego Orientation Sport Questionnaire based on how they usually feel. The challenge and skills ratings were completed 1 h before the competition, based on how they felt at the exact time of answering. In the following, the Flow State Scale-2 was completed up to 30 min after the competition they just participated, along with the challenge-skill ratings, based on how athletes felt during the competition. The results indicated that the athletes’ task orientation may be an important factor for attaining flow in competitive sport, feeling more skillful and estimating the upcoming competition as challenging, while low ego and low task oriented athletes lack these elements, which are important for them to get into flow. Additionally, not the level of task and ego orientation per se, but the balance between athletes’ goal orientation preferences seems important for the formation of flow experience, indicating that high task – high ego and high task – low ego athletes are experiencing the most positive mental state.